Phonological Acquisition in Pronouncing Indonesian Consonant Words by Two Year Old Children - Fifi Ulaimah; Wijayadi -; Waode Hamsia (Tell : Teaching of English Language and Literature Journal, 2016)
This study was about phonological acquisition, especially on phonological process theory by David Ingram. It focused on the consonant word production by three two-year-old Indonesian children. The researchers applied qualitative research methods and the data were taken from the three Indonesian children’s speech in naturalistic conversation. Based on the data analysis and interpretation, the researchers found that not all of Ingram’s phonological processes occur in the subjects’ word production. There were nine from twelve processes. In addition, the researchers also found four other phonological processes which did not reflect Ingram’s theory and there were still several sounds which were not acquired yet by the subjects at the end of her research.